The Impact of Organizational Justice Dimensions on Organizational Commitment among Bank Employees - A. Karem, Mohammed; S. JAMEEL, Alaa; Rahman Ahmad, Abd (International Journal of Psychosocial Rehabilitation, 2019)
Organizational commitment has been acknowledged as a psychological state describing the connection between an employee and his or her organization, and this state means the choice to proceed or discontinue participation in an organization. However, limited studies have been conducted in the banking sector to examine the impact of organizational justice on organizational commitment, especially in Middle Eastern countries. Purpose: of this study to examine the impact of organizational justice on organizational commitment among employee banks. Methodology: The study was conducted in the Trade Bank of Iraq, Baghdad. data collection tool by questionnaire. 177 valid questionnaires have been analyzed by SPSS software. Main Findings: showed that all three components of organizational justice, namely distributive justice, procedural justice, and interactional justice, have a positive and significant impact on organizational commitment among bank employees. Implications/Applications: The research is useful to banks that face decreased their employees’ commitment and makes the banks less afraid of decreasing employee allegiance to the bank and, on the other hand, allows it to accomplish its objectives effectively and efficiently. Originality/Novelty: This study contributes to enriching the body of knowledge in Middle East countries, particularly in Iraq and the banking sector, by examining the impact of organizational justice on organizational commitment.